2013
DOI: 10.1103/physrevlett.110.050602
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation Theorems and Entropy Production with Odd-Parity Variables

Abstract: We show that the total entropy production in stochastic processes with odd-parity variables (under time reversal) is separated into three parts, only two of which satisfy the integral fluctuation theorems in general. One is the usual excess entropy production, which can appear only transiently and is called nonadiabatic. Another one is attributed solely to the breakage of detailed balance. The last part not satisfying the fluctuation theorem comes from the steady-state distribution asymmetry for odd-parity var… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 24 publications
1
78
0
1
Order By: Relevance
“…We also define the time-reverse trajectory q † with q † (t) = q(τ − t) with q representing the mirrored trajectory with a parity for each state variable [37,38]. This trajectory starts at the mirrored state of the final state of the original trajectory: q † 0 = q τ .…”
Section: Ft In the β → 0 Limitmentioning
confidence: 99%
“…We also define the time-reverse trajectory q † with q † (t) = q(τ − t) with q representing the mirrored trajectory with a parity for each state variable [37,38]. This trajectory starts at the mirrored state of the final state of the original trajectory: q † 0 = q τ .…”
Section: Ft In the β → 0 Limitmentioning
confidence: 99%
“…(12), the probability for having no collisions, determined by the rates k(v → v) and k(−v → −v) when we have a velocity v and −v , respectively, is the same in forward and backward trajectories. Without the parity property, this is no longer the case, and as mentioned in the introduction, the theory appears to become much more involved [12,13]. Hence the corresponding terms cancel out, and we have i s = s − e s as required.…”
Section: Stochastic Thermodynamics For Kinetic Equationsmentioning
confidence: 88%
“…Spinney and Ford [42][43][44] recently investigated systems with odd dynamical variables (such as momentum that changes its sign under time-reversal operation) and found that the total entropy production can be separated into three parts, with two of them satisfying the integral fluctuation theorem. Lee et al [45,46] modified the separation rule for the total entropy production put forward in [42][43][44] and endowed each part of the total entropy production with clear physical origins.…”
Section: Introductionmentioning
confidence: 99%